Formulating Competitive Strategy in Camera Rental Competition in Malang City (Case Study on Swandudes Camera Rent Malang) - HUMAM, RAIS AULIA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aims to find out and analyze the internal and external environment in Swandudes Camera Rent, find out and analyze competitive conditions on Swandudes Camera Rent, and formulate strategic choices for Swandudes Camera Rent using the IFE, EFE, CPM, Grand Strategy Matrix and QSPM methods titled strategy formulation competitive in camera rental competitions in Malang (case study at Swandudes Camera Rent Malang) The research found that IFE 2.97 total weight score and EFE 2.75 put Swandudes Camera Rent in an internal and external position that was good enough but had plenty of room for improvisation. The results of the Competitive Profile matrix (CPM) identify that Swandudes Camera Rent is in a position that is quite competitive with its competitors. The Grand Strategy Matrix results show that Swandudes Camera Rent is in quadrant I. The recommended strategy for companies in this matrix is market penetration, product development and market development. QSPM analysis results in a market penetration strategy as the main strategy of Swandudes Camera Rent to increase its competitiveness. This research concludes that Swandudes Camera Rent can increase promotions, increase advertising burdens, increase publicity efforts and take advantage of digital marketing trends with social media in implementing market penetration strategies. Keywords: Integrated Marketing Communication, Service Quality, Purchase Decisions